Public Contracts as Accountability Mechanisms: Assuring quality in public health care in England and Wales - David Hughes (Public Management Review, 2016)
Public sector contracts are designed to strengthen the accountability of service providers to their funders. It is claimed that quality is improved by the use of mechanisms such as service specifications, monitoring of performance and imposition of contractual sanctions. However, socio-legal and economic theories of contracting suggest that it will be difficult to write and enforce contracts to achieve this. This paper reports the results of a study of National Health Services contracting in England and Wales that suggests that contracts in themselves will not improve accountability – collibration of overlapping modes of regulation, including hierarchical governance via performance targets, is required.